2023
DOI: 10.3390/app13074382
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Extrinsic Factors Affecting the Color of Fresh Beef Meat—Comprehensive Review

Abstract: Meat color research from the last two decades suggests that a combination of different intrinsic (ultimate pH, age of the animals, muscle position, breed, slaughter weight, and sex) and extrinsic factors (production systems and feeding, pre-mortem stress, slaughter season, and chilling rates) might have a deep impact in the color of beef muscle and influence consumers’ acceptance of fresh meat. Ultimate pH and muscle position were perceived as the most determinant intrinsic factors, whereas production systems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 109 publications
1
4
0
Order By: Relevance
“…Conversely, lighter animals may be more sensitive to pre-mortem stress, due to lower pre-mortem glycogen reserves [26], which may result in lower intra-muscular lactic acid accumulation. Such circumstances can often be associated with higher ultimate meat pH values [30]. Our findings confirmed that heavier animals (AW > 445 kg) tended to achieve slightly lower meat pH values (Table 6).…”
Section: Animal Weight (Aw)supporting
confidence: 84%
See 1 more Smart Citation
“…Conversely, lighter animals may be more sensitive to pre-mortem stress, due to lower pre-mortem glycogen reserves [26], which may result in lower intra-muscular lactic acid accumulation. Such circumstances can often be associated with higher ultimate meat pH values [30]. Our findings confirmed that heavier animals (AW > 445 kg) tended to achieve slightly lower meat pH values (Table 6).…”
Section: Animal Weight (Aw)supporting
confidence: 84%
“…DFD meat is characterized as having higher ultimate pH values, increased water holding capacity, and lower L*, a*, and b* color readings [26,27]. DFD-related problems are mostly due to reduced lactic acid accumulation in post-mortem muscle, which is precipitated by insufficient pre-mortem glycogen reserves [28][29][30]. This situation may also trigger the release of catecholamines in post-mortem muscle and negatively affect meat texture [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in the lightness values of supplemented chicken nuggets was due to the addition of liver, whose increasing amount in the treatments resulted in the darkness of the final product. Because the liver contains more myoglobin than meat and stores different pigments, it is darker than meat ( Llauger et al, 2023 ; Poveda-Arteaga et al, 2023 ). Texture is another key factor in determining the perceived value of a food product in terms of its exterior appearance.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known the animal’s diet has an important effect on beef’s fatty acid profile. Diverse studies indicate animals fed on pastures have beef with a darker color ( Poveda-Arteaga et al, 2023 ), leaner and less infiltrated fat, and a lower percentage of monounsaturated fatty acids in the subcutaneous fat ( Noci et al, 2007 ). Likewise, the ω-6:ω-3 ratio decreases while the ω-3 and α-linoleic fatty acids increase ( Aurousseau et al, 2007 ).…”
Section: Chilean Beef Quality and Chilean Consumer’s Preferencesmentioning
confidence: 99%